Study on the Effect of the Curvature of Solar Collector on Wind Loading Coefficients and Dynamic Response of Solar Collector - Kazem, Aladine Abdulkader; Hussein, Khalid Hameed (Al-Khwarizmi Engineering Journal, 2013)
In the current research, the work concentrated on studying the effect of curvature of solar parabolic trough solar collector on wind loading coefficients and dynamic response of solar collector. The response of collector to the aerodynamic loading was estimated numerically and experimentally. The curvature of most public parabolic trough solar collectors was investigated and compared. The dynamic response of solar collector due to wind loading was investigated by using numerical solution of fluid-structure interaction concept. The experimental work was done to verify the numerical results and shows good agreement with numerical results. The numerical results were obtained by using finite element software package (ANSYS 14). It was found that the change in collector curvature (focal length) lead to remarkable changes in wind loading coefficients (drag, lift, and moment), dynamic response (displacement) and natural frequencies but does not affect the first mode shape.